M. C. Higgins, the great - Hirschman, Susan (New York : SCHOLASTIC INC., 1996)
Mayo Cornelius Higgins sits on his gleaming, forty-foot steel pole towering over his home on Sarah's Mountain. Stretched before him are rolling hills and shady valleys. But behind him lie the wounds of strip mining, including a mountain of rubble that may one day fall and bury his home.
Mayo Cornelius Higgins se sienta en su brillante poste de acero de cuarenta pies sobre su casa en la Montaña de Sarah. Extendidos ante él, hay colinas y valles sombreados. Pero detrás de él se encuentran las heridas de la franja, incluyendo una montaña de escombros que algún día puede caer y enturbiar su hogar.
Keywords: NORTH AMERICAN LITERATURE -- NOVEL; LITERATURA NORTEAMERICANA -- NOVELA